PERAN FISIOTERAPI DALAM MENGURANGI NYERI PADA OTOT DAN SENDI PADA CIDERA OLAHRAGA YANG SERING DIALAMI REMAJA DI SMAN 5 PEKANBARU - Marliana; Tonis, Marian; Aziz, Abdul (LPPM Universitas Awal Bros, 2024)
Sports injuries are a common health issue among adolescents, especially high school students who are actively engaged in physical activities. Muscle and joint injuries can cause pain, limited mobility, and interfere with academic and social activities. This community service program aims to provide education and simple physiotherapy treatments to students at SMAN 5 Pekanbaru to help reduce pain and prevent recurrent injuries. The methods used include health education, demonstrations, and hands-on practice of physiotherapy techniques such as stretching, cold/hot compresses, and muscle strengthening exercises. The results showed an increase in students' understanding of sports injury management and a reduction in pain complaints after participating in the therapy. This program is expected to raise awareness of the importance of proper injury management and the role of physiotherapy in maintaining adolescents physical health.